PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PEMADAM KEBAKARAN KOTA BATAM - sunarsan sitohang (STIE AMKOP, 2019)
In every organization or company there are always obstacles in the process of achieving performance. It should be understood that the expected performance of an employee is not easy because it is influenced by various factors of compensation, satisfaction, motivation, work environment, and many other factors. Based on these factors, a study was conducted under the title Effect of Work Environment on Fire Performance in Batam City. This study aims to determine the effect of the work environment on fire fighting performance in Batam City. The data analysis method used is a simple linear regression statistical analysis and uses the t test to analyze the closeness of the relationship of individual variables, while testing the instrument using the validity test and reliability Statistical test results show that the relationship of the work environment to employee performance is positive (unidirectional). Based on the t test results obtained a significant value of 5% then H1 is accepted or H0 is rejected. This means that the work environment, which in this study was discussed more will the availability of hydrant affect the performance of firefighters in Batam City.